Spatiotemporal assessment of pathogenic Leptospira in subtropical coastal watersheds - Ronell Bridgemohan; Matthew J. Deitch; Emily Harmon; Matt R. Whiles; P. Christopher Wilson; Eban Bean; Puran Bridgemohan; Joseph H. Bisesi; Jodel Nicholas; Aaden Redhead; Dave S. Bachoon (IWA Publishing, 2024)
The World Health Organization classifies leptospirosis as a significant public health concern, predominantly affecting impoverished and unsanitary regions. By using the Pensacola Bay System as a case study, this study examines the underappreciated susceptibility of developed subtropical coastal ecosystems such as the Pensacola Bay System to neglected zoonotic pathogens such as Leptospira. We analyzed 132 water samples collected over 12 months from 44 distinct locations with high levels of Escherichia coli (>410 most probable number/100 mL). Fecal indicator bacteria (FIB) concentrations were assessed using IDEXX Colilert-18 and Enterolert-18, and an analysis of water physiochemical characteristics and rainfall intensity was conducted. The LipL32 gene was used as a quantitative polymerase chain reaction (qPCR) indicator to identify the distribution of Leptospira interrogans. The results revealed 12 instances of the presence of L. interrogans at sites with high FIB over various land cover and aquatic ecosystem types. Independent of specific rainfall events, a seasonal relationship between precipitation and elevated rates of fecal bacteria and leptospirosis was found. These findings highlight qPCR's utility in identifying pathogens in aquatic environments and the widespread conditions where it can be found in natural and developed areas. HIGHLIGHTS The study utilized qPCR assays to detect pathogenic Leptospira in various aquatic ecosystems, revealing its presence in diverse habitats throughout the year, particularly in developed environments and smaller water bodies like streams and bayous.; Leptospira occurrence showed correlations with certain water quality parameters.; The research highlights the public health risks associated with Leptospira contamination in recreational water bodies, suggesting that relying solely on traditional fecal indicator bacteria may underestimate microbial risks.; The study emphasizes the efficacy of qPCR in detecting waterborne pathogens like Leptospira, supporting the "One Health" approach that advocates for multidisciplinary collaboration to address complex health issues at the intersection of human, animal, and environmental health.;